Students’ Speaking Skill in Informative Speech at first Semester Students of Development Economics of STIE-SAK Academic Year 2024/2025 - Yelnim, Yelnim; Wijaya, Sukarta Kartawijaya (The Future of Education Journal, 2024)
In this research, the writer used descriptive research to analyze the students’ speaking skill in informative speeech. This research was done in order to get description about students’ ability in informative speech. The writer analyzed and described the students’ skill in using speech especially in informative speech. The students used figurative speech in his/her speaking. The population of this research was the students at first semester of Development economics of STIE-SAK academic year 2024/2025, the total of population was 10 students. The instruments of this research were speaking test and questionnaire. From the finding, the result of the test showed that there was no student got A, one students got B (10 %), five students got C (50 %), three students got D (30 %), and there was one student got E (10 %). The students’ speaking skill was in average grade because the mean score was in average score, that was 60, 4 %. The result of questionnaire, it was found that the total checklist of the respondents were in sometime (94) checklist, often (26) checklist, always (15) checklist, rarely (13) checklist, and never (1) checklist. The students faced problems in all of speaking indicators namely grammar, vocabulary, comprehension, fluency and pronunciation.